Optimization of teachers' digital competence in the development of wordwall as interactive learning platform - Prasart Nuangchalerm (CV. SPDFHarmony, 2025)
Background: The rapid advancement of digital technology necessitates that teachers enhance their digital competence to create more engaging learning experiences. Interactive learning media, such as Wordwall, provide opportunities to integrate technology into teaching.Aim: This study aims to optimize teachers' digital competence through the development of a valid and practical interactive Wordwall-based learning media.Method: This study employed research and development (R&D) using the ADDIE model. The research subjects involved eighth-grade teachers and students, with four mathematics teachers and six students selected through purposive sampling. Data collection included expert validation, practicality tests with teachers and students, and teacher interviews. Additionally, qualitative data from teacher interviews provided deeper insights into the platform’s impact on their digital competence.Results: The validation results indicate that Wordwall has a high level of validity, with an average score of 90% (highly valid), covering content suitability, construction, language, and technology aspects. The practicality test demonstrated that Wordwall is practical for both teachers and students, with average scores of 77.45% and 82.75%, respectively (practical). Additionally, a survey assessing the optimization of Wordwall usage by teachers yielded an average score of 77.6% (good). Teacher interviews revealed that Wordwall enhances their confidence in utilizing digital technology.Conclusion: Wordwall serves as a valid and practical interactive learning platform that supports the optimization of teachers' digital competence. It enables teachers to integrate technology into their teaching, enhancing their confidence and instructional strategies. Future research is recommended to explore the long-term impact on teachers' digital competence and investigate its application across diverse educational contexts.